2018
DOI: 10.12659/msm.908510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Allograft Inflammatory Factor-1 (AIF-1) in Hepatocellular Carcinoma

Abstract: BackgroundAllograft inflammatory factor-1 (AIF-1) is a cytoplasmic protein cloned from activated macrophages in human and rat allografts. AIF-1 has been identified as a modulator of inflammatory response, and recently published studies have shown its increased expression in carcinogenesis. However, there are still limited data on the potential functional role of AIF-1 in hepatocellular carcinoma (HCC).Material/MethodsWe evaluated the expression of AIF-1 in 104 cases of paired HCC and adjacent non-cancerous liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We also found that the AIF-1 expression level in NSCLC tissue was positively associated with malignant characteristics such as lymph node metastasis, and TNM stage. This finding is in line with previous data obtained for hepatocellular carcinoma [ 34 ]. Furthermore, lymph node involvement was associated with an elevated serum level of AIF-1 in patients with cervical cancer [ 35 ], supporting the proposal that AIF-1 may be a marker of more aggressive tumor behavior.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that the AIF-1 expression level in NSCLC tissue was positively associated with malignant characteristics such as lymph node metastasis, and TNM stage. This finding is in line with previous data obtained for hepatocellular carcinoma [ 34 ]. Furthermore, lymph node involvement was associated with an elevated serum level of AIF-1 in patients with cervical cancer [ 35 ], supporting the proposal that AIF-1 may be a marker of more aggressive tumor behavior.…”
Section: Discussionsupporting
confidence: 94%
“…Whilst not a marker of stemness, MMP9 is linked with EMT as it plays a key role in degradation of the extracellular matrix and therefore by aiding the escape of epithelial tumor cells from their location of origin, MMP9 expression has been linked to the metastatic potential of HCC cells [53]. AIF-1 has been shown to promote proliferation and migration of breast cancer cells [54,55], and whilst its role in HCC remains unknown, increased mRNA levels in HCC tumor cells have been observed [56]. Presence of TA-AAbs to the majority of these antigens in HCC patients have previously been described [15,20,[57][58][59].…”
Section: Plos Onementioning
confidence: 99%
“…This molecule orchestrates both immune (i.e., controlling proliferation, the migration and polarization of T lymphocytes, and the activation of macrophages or microglia or modulating dendritic cells) and non-immune actions (i.e., modulation of membrane ruffling, activation of endothelial cells, cell cycle progression and F-actin binding activity) [44]. The role of AIF-1 in cancer has been demonstrated in past works, mainly focused on hepatocellular carcinoma [45], breast [46], lung [47] and other types of cancer [48][49][50]. To our best knowledge, no studies have been conducted to understand the carcinogenic role and prognostic value of AIF-1 in pancreatic cancer; a recent study [51] revealed that AIF-1 acts as a robust diagnostic and prognostic biomarker in several types of cancer and is closely correlated with tumor immune infiltration.…”
Section: Discussionmentioning
confidence: 99%